Credit and women's group membership in South India: Testing models of intrahousehold allocative behavior - Nathalie Holvoet (Feminist Economics 11(3), November 2005, 27 - 62, 2005)
This article uses empirical data from the author's own South India household survey, which compares the impact of slightly diverging credit schemes u pon selected indicators of allocative behavior to test the value added of an economic institutional approach for modeling intrahousehold allocation. It is argued that the income-pooling test and conventional neoclassical household models inadequately picture what happens within households as they start from the premise that behavior is built solely upon free agency. An alternative economic institutional approach is proposed and an expanded test framework is set out. Empirical research findings show that unveiling decision-making processes may indicate why individuals act as if they hold common preferences. The article suggests that changes in selected allocative outcomes occur mainly as a result of changes in underlying allocative processes and further demonstrates that membership in women's groups is one effective way of changing intrahousehold decision-making processes and outcomes.